Pomegranate (Punica granatum L,) wine polyphenols affect Nrf2 activation and antioxidant enzyme expression in human neuroblastoma cells (SH-SY5Y) - Li, Xuan; Liu, Linwei; Pischetsrieder, Monika (Journal of Functional Foods, 2017)
Pomegranate (Punica granatum L.) phenolic compounds may prevent oxidative stress-induced neurodegenerative diseases. The present study investigated cytoprotective effects of pomegranate wine extracts and their phenolic compounds in neuroblastoma cells SH-SY5Y. The extracts significantly activated nuclear factor erythroid 2-related factor 2 (Nrf2; ≤2.6-fold) and inhibited nuclear factor κB (NF-κB) nuclear translocation (≥26% activity) without cytotoxic effects. Moreover, pomegranate wine extract time-dependently elevated heme oxygenase-1 (HO-1) expression (≤2.9-fold) and promoted superoxide dismutase (SOD) activity (≤1.4-fold), while it had no significant effect on glutathione peroxidase (GPx) activity. The main phenolic components of the extracts, gallic acid, ellagic acid, and punicalagin also led to a significant inhibition of NF-κB and the activation of Nrf2 translocation and subsequent increase of HO-1 expression and SOD activity, dependent on concentration and incubation time. Thus, pomegranate wine and its phenolic components may have a protective effect on neuronal cells by triggering Nrf2 and inhibiting NF-κB signaling.
Keywords: Pomegranate (Punica granatum L.); polyphenols; neuroblastoma cell; Nrf2; antioxidant enzyme